2010
DOI: 10.1016/j.chemosphere.2009.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Mass balance for POPs in hazardous and municipal solid waste incinerators

Abstract: The amount of different persistent organic pollutants (POPs) in the input of waste incinerators was compared to that in the output. Three cases were considered: a rotary kiln incinerating hazardous waste, a grate furnace incinerating municipal solid waste (MSW) and the same grate furnace co-incinerating plastics of waste of electrical and electronic equipment (WEEE) and automotive shredder residue (ASR) with MSW. The mass balance for PCBs in the rotary kiln indicates that these POPs are destroyed effectively d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 25 publications
2
31
0
Order By: Relevance
“…These findings are consistent with results from other authors, concluding that the POP-output of an incineration process is to a great extent independent from the POP concentration in the incinerated waste [60,96]. Moreover, if wastes such as ASR, containing high levels of POPs, are co-incinerated with for instance MSW, the incinerator is a POP sink, as less POPs are formed than destroyed [39,99]. New formation of PCDD/Fs upon cooling of the flue gas occurs via the heterogeneous pathway either through the precursor mechanism or through de novo synthesis.…”
Section: Major Environmental Concerns When Asr Is Co-incineratedsupporting
confidence: 94%
See 1 more Smart Citation
“…These findings are consistent with results from other authors, concluding that the POP-output of an incineration process is to a great extent independent from the POP concentration in the incinerated waste [60,96]. Moreover, if wastes such as ASR, containing high levels of POPs, are co-incinerated with for instance MSW, the incinerator is a POP sink, as less POPs are formed than destroyed [39,99]. New formation of PCDD/Fs upon cooling of the flue gas occurs via the heterogeneous pathway either through the precursor mechanism or through de novo synthesis.…”
Section: Major Environmental Concerns When Asr Is Co-incineratedsupporting
confidence: 94%
“…Co-incineration of ASR may indeed lead to the release of POPs, due to the elevated concentrations of chlorine, POP-precursors and POPs contained in the ASR (Section 3). Several studies investigated the influence of co-incineration of ASR on POP emissions [39,40,60,[96][97][98][99]. It is generally assumed that the incoming POPs are destroyed during incineration and that upon cooling of the flue gases new POPs form via the heterogeneous pathway either through the precursor route or through de novo synthesis [100][101][102].…”
Section: Major Environmental Concerns When Asr Is Co-incineratedmentioning
confidence: 99%
“…Table 9 showed the annual mass balance of PCDD/Fs and emission factors over the whole cement production process, according to the operating parameters (Table 1) and data from Tables 6, 7 and 8. Some studies also conducted on the mass balance of PCDD/Fs in MSWI and they concluded that MSW incinerators can act as PCDD/F sinks, depending on the PCDD/F concentrations in the waste, on the operating conditions and on the APCDs (Van Caneghem et al, 2010). In this study, mass balance indicated that annual net formation and release of PCDD/Fs from the cement kiln was ca.…”
Section: Solid Samplesmentioning
confidence: 86%
“…The amount of PCDD/Fs transported through air is so high that some of the water treatment plants have been suggested to put on a cover (Lin et al, article in press). In order to discover the PCDD/Fs contribution to the environment of several PCDD/Fs emitting activities, the fates of PCDD/F -like compound and PCDD/Fs have been studied for years (Tsai et al, 2001;Kuo et al, 2003;Van Caneghem et al, 2010). Since tighter emission limits have been applied to incinerators, sinter plants have become the dominating PCDD/F emission sources .…”
Section: Introdutionmentioning
confidence: 99%